Molecular dissection of box jellyfish venom cytotoxicity highlights an effective venom antidote - Man-Tat Lau (Nature Portfolio, 2019)
Box jellyfish venom causes tissue damage, pain, and death through unknown molecular mechanisms. Here, Lau et al. perform a CRISPR screen to identify genes required for venom action and use this information to develop an antidote that blocks venom-induced pain and tissue damage in vivo.